Fighting the COVID-19 Crisis: Debt Monétisation and EU Recovery Bonds - Alberto Botta; Eugenio Caverzasi; Alberto Russo (Intereconomics)
Abstract This paper highlights some peculiar characteristics of the economic crisis induced by the spread of COVID-19. It suggests two intertwined policy measures in order to tackle the emergency phase of the crisis and to support the economy in the subsequent recovery phase. The proposed short-term policy measures offer policy responses in the event of a second wave of coronavirus infections in the coming months. In the aftermath of the emergency phase, the current proposal puts forward the implementation of a massive EU-wide recovery plan addressing the long-lasting technological and environmental challenges of these years, which will be financed by European institutions through the issuance of European Pandemic Recovery Bonds.